Pengaruh Model Picture and Picture terhadap Evaluasi Kosakata Bahasa Inggris Kelas III di SD Negeri Periuk 3 - Ina Magdalena; Rahma Sekar Kusumawaty; Silmi Rufaidah; Syahda Nurul Rabbani (Jurnal Halaqah, 2020)
This study studies to learn whether there are learning models and pictures for English. This research was conducted on students in grade III of SD Negeri Periuk 3. The method used in the study was. The method was chosen because the main purpose of this research is to study the facts arising from aid from a treatment. The hypothesis proposed about the effect of drawing and drawing models is very impactful for students in doing vocabulary learning. However, based on data obtained from the results of research models, images and drawings very much refer to the English vocabulary.